(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2021)
Objective: report the case of a critical patient with COVID-19 and show the main findings related to the injury considered acute skin failure (ASF), as well as perform his differential diagnosis with preventable pressure injury (PI). Method: observational, longitudinal, case report type study, developed in a hospital in São Paulo, in the intensive care unit (ICU) exclusively for people diagnosed with COVID-19. Data were collected from a single patient between March and September 2020. Results: A patient with complications from COVID-19 developed a skin lesion, initially defined as PI and later reclassified as ASF. The following findings corroborated the diagnosis: prolonged invasive mechanical ventilation, respiratory, renal and cardiac insufficiency and sepsis of respiratory focus. In addition, other aggravating factors, such as the use of vasoactive drugs, hemodynamic instability with intolerance to minimal repositioning, prolonged fasting and disseminated intravascular coagulopathy associated with coronavirus infection. Conclusion: the report shows that there are difficulties for the differential diagnosis between ASF and PI in clinical practice. This is a new concept, and it is essential that health professionals recognize the main factors associated with the appearance of ASF, many of which are also related to the development of PI, highlighting the need for individualized analysis of these injuries, and ensuring the implementation of interventions for prevention and treatment.